Kilka uwag o problematyce komunikatywności tekstów prawnych - Nieciecka, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Legal language is a specific code that is used by the legislator to regulate social relations. This specific code helps law come to life. While it should reach to all of us, in practice it is understood by minority of our society. The code, whose users employ three times fewer words than the national language users do and build sentences about four times longer. Characteristics of the legal language create the need of the legislator to pay more attention to his creative work than the users of any other language. Correct legal writing means striking a balance between two different values. Legal texts need to be plain and understandable for as many people as possible but on the other hand the reality should be described precisely to the maximum. Awareness of those characteristics enables to pass a law that is clear, precise, comprehensible and flexible for the future. If the legislator follows not only the rules of correct legislation, but also the rules of the language correctness, his communication with people under his jurisdiction becomes fast and trouble-free. At the same time, it ensures a stability of law and gives citizens a feeling of legal safety. The present situation, where legal acts become clear and understandable after their interpretation by jurisprudence and doctrine, leaves much to be desired.First of all, a solution to the problem of linguistic correctness of legislation in Poland should include raising linguistic competence of persons involved in the legislative process. It is necessary to create a unit which will be responsible for the linguistic sphere of law. The legislator should engage in the legislation process a widest possible group of people who could pay attention to any ambiguities and contradictions in the legal texts. Studying legal language should also be a compulsory element of law studies in our country. The legislator should understand that it is worth spending a little more time to create a correct, understandable legal texts because the brightness and clarity of the law is a fundamental condition to state about its compliance with the rule of democratic right’s state.
Keywords: legislator; język prawny; język prawa; tworzenie prawa; legislacja; język ustaw; elastyczność; jasność; zrozumiałość; komunikatywność; ustawodawca; kompetencja językowa